Mapping Language Function in the Brain: A Review of the Recent Literature - Crafton, Robert E. and Kido, Elissa (Journal of Technical Writing and Communication, 2000)
Advocates of brain-based learning have argued that instructional methods, to be successful, must be based on an understanding of how the brain processes information. In the past most descriptions of neurocognitive function were largely speculative, relying on theoretical constructions of how we believed the brain to work. Recent advances in functional imaging—Positron Emission Tomography and Magnetic Resonance Imaging—have, however, opened the brain to empirical study. This article will consider the potential importance of brain study for composition instruction, briefly describe functional imaging techniques, and review the findings of recent brain-mapping studies investigating the neurocognitive systems involved in language function. In short, understanding how language systems are organized in the brain represents the first step in our attempts to create brain-compatible instructional methods in the composition classroom. Following a review of the recent literature, the article will consider the possible implications of this information for pedagogical practice.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC93NjgyLXIwbWItNjd2YS05cms1